From promise to practice. A landscape perspective on discrepancies between permit documentation and built solar power plants - Enserink, Merel; Klaaskate, Vincent; Oudes, Dirk; Stremke, Sven (Landscape research, 2025)
Over the past years, the implementation of solar energy technology in the landscape has increased significantly. Landscape quality, an objective for solar power plant (SPP) development in the Netherlands, is therein potentially compromised. In this study, we examine the discrepancies of five Dutch SPPs through post-occupancy evaluation and structured interviews. We found 79 discrepancies in spatial measures. Interviewees attributed discrepancies to the business case, permit procedures, regulation, enforcement, and maintenance. We make two recommendations to improve policy and simultaneously strengthen the mandate of landscape planning and design with regard to SPP development. First, broader societal concerns need to be better defined as permit requirements to prioritise them in SPP development. Secondly, design visualisations by landscape architects need to consider temporal aspects to foster communication and transparency among stakeholders. These changes in policy and SPP development practice are needed to maintain landscape quality as stipulated for example, by the European Landscape Convention.